Influence of exogenous treatment with antioxidants on dynamics of phenolic compounds during storage of apples - Сердюк, Марина Єгорівна; Калитка, Валентина Василівна; Байбєрова, Світлана Сергіївна (Eastern-European Journal of Enterprise Technologies, 2014)
The changes in the content of phenolic compounds in apple fruits during maturation on the maternal plant and storage in the refrigerator were studied. It was found that the average content of phenolic substances in picking-maturity apples, grown in the south-steppe subzone of Ukraine was at the level of 192.41 mg/100 g. Analysis of variance has confirmed that the accumulation of phenolic compounds in apples is significantly influenced (with a share of 37.3 %) by weather conditions for fruit formation. The main weather factor that most affects the content of phenols in picking-maturity apples is the average sum of effective temperatures above 10 °C. During storage of fruits, phenolic compounds also undergo significant changes. In the first 4-5 months of storage, in apples there is an increase in the content of phenolic compounds, which is caused by post-harvest ripening of fruits. The maximum amount of phenols was observed on the 120th day of storage in control fruits for grades Idared and HoldenDelishes and on the 150th day - grades Reinette Simirenko and Florina. These periods coincide with reaching full harvest maturity and the highest P-vitamin value of apples. Further, overripening processes of fruits, accompanied by a reduction in content of phenolic compounds begin. Treatment with antioxidant compositions lowers the activity of polyphenol oxidase and slows down the oxidation of phenolic compounds. Analysis of variance has revealed that the final content of phenolic compounds at the end of storage of apples was predominantly influenced by weather conditions for the fruit formation with 40.5% share of influence. Exogenous treatment with antioxidant compositions eliminates the influence of many weather factors on saving phenolic compounds and simplifies forecasting. The models for forecasting the content of phenols in picking-maturity apples and after the storage process, depending on weather factors were developed.